ANALISA PEMBEBANAN JEMBATAN MENGGUNAKAN SOFTWARE SAP2000(Studi Kasus: Jembatan Panglima Sampul. Kec. Tebing Tinggi. Kab. Kepulauan Meranti ) - Hamzah; Basir, Noerdin (Jurnal TeKLA: Jurnal Inovtek Seri Teknik Sipil dan Aplikasi, 2024)
Transportation infrastructure is essential tomake human activities faster and easier. Bridge buildings are a very important component of transportation infrastructure. Bridges have main function to connect two areas that are blocked by obstacles,such as rivers, valleys, straits or seas, channels, highways, and railways.railroad. Panglima Sampul Bridge is one of them, because it connects the road between areas that are cut off by the river.between areas that are cut off by the river. In this study aims to determine how much load occurs on the panglima sampul bridge using SAP2000 software.using SAP2000 oftware. From the results of the analysis carried out, the value of the dead load itself was obtained (MS) 375.82 kN, additional dead load (MA) for asphalt + overlay layers 6.6 kN / m², sidewalks13.75 kN, raling pipe 0.803 kN, pedestrian 12.5 kN, and truck load 6.75 kN/m².evenly divided 6.75 kN/m², centered line load 67.62 kN/m and Brake force 146.5kN. for the results of the SAP2000 analysis, the largest compressive force is obtained in strong conditions, namely 3874.88 kN.strong condition, namely 3874.88 kN / m in the service condition of 2142.92. For the largest tensile forcein strong condition 1763.5 kN / m in service condition 1111.29 kN / m. For the moment  is 619.56 kN and for the largest shear is 497.73 kN/m.